Síndrome de carga del cuidador (2007)
ABSTRACT: Introduction: Physical and psychological discomfort experimented by caregivers of patients with some degree of brain damage is closely related to their role. Studies from countries other than Colombia show a highly vulnerable population, with poor coping strategies. Objective: To stress the fact that the concept of caregiver burden syndrome (CBS) has not been discussed as to its validity and usefulness. In consequence, there are a great many theoretical and methodological differences regarding its management. Method: An essay-type presentation is made, describing the more significant data arising from studies done on the subject looking for information that can help explain the etiology of the syndrome, differentiating it from other syndromes. The most appropriate and efficacious interventions are also considered, and controversy surrounding the subject is discussed as well. Conclusion: The difference in variables contributing to the appearance of the CBS establish, once more, that when trying to explain its causes factors related to the burden and the differences between caregivers must be taken into account.